2014
DOI: 10.1016/j.expneurol.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hydrocephalus alters the cytoarchitecture of the adult subventricular zone

Abstract: Hydrocephalus can develop secondarily to a disturbance in production, flow and/or absorption of cerebrospinal fluid. Experimental models of hydrocephalus, especially subacute and chronic hydrocephalus, are few and limited, and the effects of hydrocephalus on the subventricular zone are unclear. The aim of this study was to analyze the effects of long-term obstructive hydrocephalus on the subventricular zone, which is the neurogenic niche lining the lateral ventricles. We developed a new method to induce hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…It has been reported that aging gradually affects the number, size, and composition of these structures suggesting that, through their interaction with NSCs, fractons could be related to the loss of neurogenesis during aging (Kerever et al, 2015 ). According to this, changes in fractone ultrastructure have been described in an experimental obstruction model of hydrocephalus in mice, which showed decreased NSCs proliferation in the SVZ (Campos-Ordoñez et al, 2014 ). Future studies will provide a more comprehensive understanding on the function of fractones in the neurogenic niche.…”
Section: Aging Disrupts the Svz-rms Axismentioning
confidence: 96%
“…It has been reported that aging gradually affects the number, size, and composition of these structures suggesting that, through their interaction with NSCs, fractons could be related to the loss of neurogenesis during aging (Kerever et al, 2015 ). According to this, changes in fractone ultrastructure have been described in an experimental obstruction model of hydrocephalus in mice, which showed decreased NSCs proliferation in the SVZ (Campos-Ordoñez et al, 2014 ). Future studies will provide a more comprehensive understanding on the function of fractones in the neurogenic niche.…”
Section: Aging Disrupts the Svz-rms Axismentioning
confidence: 96%
“…NO is also important for the structural maintenance of the periventricular subependymal zone. 77 It may therefore be worthwhile to focus on elevated NO expression in microgravity as well as in gravity simulation experiments by rat tail suspension or during human HDT. 78…”
Section: Space Flight Diseasementioning
confidence: 99%
“…Intraventricular hemorrhage (IVH) arises from rupture of immature and developing blood vessels in the germinal matrix of premature infants. IVH occurs in up to 25% of preterm neonates where 10% of events are further complicated by hydrocephalus (Campos-Ordonez et al, 2014 ; Koschnitzky et al, 2018 ). A recent NIH workshop on post-hemorrhagic hydrocephalus (PHH) reported that IVH affected neonates develop somatic growth impairment, white matter damage, motor dysfunction and neurocognitive deficiency (Koschnitzky et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%